“El sistema penitenciario y su incidencia en los derechos humanos de las personas privadas de la libertad del centro de privación de la libertad de Riobamba durante el periodo de enero a septiembre de 2015.” - Chimbo Shiguango, Alex Reinaldo (2017)
This research aims to determine the impact of the system of Social rehabilitation in the human rights of persons who have been sentenced for various crimes and that meet this sentence in the center of imprisonment for adults in conflict with the law of Riobamba. For this purpose applied surveys to 40 persons deprived of liberty in a pavilion of the CPLPACLR, 6 judges of the criminal law with the purpose of unambiguous data for this research work. Chapter I, the Reference Framework in which, the approach to the problem is to investigative the overall objective, specific objectives, the problem justification and importance. Chapter II, the Theoretical Framework was conducted and developed themes and subthemes objects of this investigative work with the following topics, unit I, item 1 prison system; unit II was developed the responsible subject to the execution of sentences and rehabilitation; Unit III the reintegration social of the people deprived of liberty; Unit IV the penitentiary system and its impact on the human rights of the freedom of privative persons; Unit V unit hypothetical, here develops the operationalization of variables and the definition of basic terms. Chapter III, the methodological framework, which explains the basic form of the research, the type of research that was conducted, methods of research, the population sample and shows the collected information in the research place; techniques and instruments of gathering and analysis of data and last is the procedure techniques, analysis and discussions of results. Finally, Chapter IV the Conclusion and Recommendations product of the analysis of the prison system and its impact on the human rights of persons deprived of freedom field of the research work we have.